Statutory Recognition Provisions in Britain, 1976-1980 - Beaumont, P. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper assesses the extent to which the union movement in Great Britain was able to realise in practice the potential advantages of the statutory recognition provisions.